IMPLEMENTASI PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN PRESTASI BELAJAR SISWA DI SMP MUHAMMADIYAH 1 KOTA PROBOLINGGO - Baqi, Ahmad Fuad Abdul (e-Journal STAI Muhammadiyah Tulungagung, 2015)
Education is an anticipatory action, because what is done in education will now be applied in human life in the future. Therefore education today should be able to address issues and solve the problems faced especially at this time. Education is not a simple effort but rather an activity that is dynamic and full of challenges. Therefore SMP Muhammadiyah 1 Kota Probolinggo in this case is one of many educational institutions are considered to be a reference and the choice of the people in the study because of religious education are much in demand by the public. Therefore, the author wishes to make SMP Muhammadiyah 1 Kota Probolinggo as an object of research, especially in the field of Islamic religious education that includes learning methods, the professionalism of teachers and school facilities. To further the author presented in the form of a thesis with the title. Implementation of Islamic Education in Improving Student Achievement in SMP Muhammadiyah 1 Kota Probolinggo